If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 15) + -5 = 6x + 10 + 3x Reorder the terms: 3(15 + 3x) + -5 = 6x + 10 + 3x (15 * 3 + 3x * 3) + -5 = 6x + 10 + 3x (45 + 9x) + -5 = 6x + 10 + 3x Reorder the terms: 45 + -5 + 9x = 6x + 10 + 3x Combine like terms: 45 + -5 = 40 40 + 9x = 6x + 10 + 3x Reorder the terms: 40 + 9x = 10 + 6x + 3x Combine like terms: 6x + 3x = 9x 40 + 9x = 10 + 9x Add '-9x' to each side of the equation. 40 + 9x + -9x = 10 + 9x + -9x Combine like terms: 9x + -9x = 0 40 + 0 = 10 + 9x + -9x 40 = 10 + 9x + -9x Combine like terms: 9x + -9x = 0 40 = 10 + 0 40 = 10 Solving 40 = 10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5(4-3x)=4(-4x+2) | | 5x-6+2x+4=x | | -1-2y+4=0 | | y^2-10y+25=-16 | | (-1.4)-5.2-5.1= | | 7(p-4)+p=2(p-2) | | 5x-6-2x+4=x | | 5-0.3t=2.1+0.5(t-1) | | 60x+45-x=15x+225-75-120 | | 2(1-5v)=7(v+3)-2 | | 31=4y+3 | | -3x+16=0 | | x/2-13=-9 | | 7+7(8+4r)=r-5(1-2r) | | 0=13x^2+1300 | | 27x+6=17x-26 | | x^2+13-1280=0 | | x*0.21=y | | 4(3k-4)=-3(k-4)+8k | | 2+8x=11x-13 | | 17+4(3a-2)=9 | | -7(m-3)=-5(m+1) | | 6+2p-7=-4(p-5)+5(-2-p) | | 3x-5=10+7x | | 3(x-4)-4(x-3)=x+3-(x-6) | | 7(2k-3)+5(1-3k)=-1-3k+3 | | 12p+p=2-2p | | 8-9x=27 | | -7b-3=-3b+5 | | -4(1+8p)=-4p+3(8-7p) | | -2-2y+8=0 | | 2(3x-5)+7=4-9(x-1) |